Misinterpreting modern Russia - Sergi, Bruno S. (Continuum, 2009)
When President Vladimir Putin ascended to the Kremlin at the end of the 1990s, he had to struggle with the after-effects of Boris Yeltsin''s political agenda: outrageous corruption, endless social injustice, and deeply entrenched interests dating back to Gorbachev and beyond. From the outset, Putin saw his task as leveling out the political scenery. Discontent had been building up among ordinary Russians on these consequences of the dramatically unstable 1990s. Stabilization of the political system and cleaning up the widespread corruption were Putin''s aims, and the Russian people supported h.